MATERIALS FOR TEACHING WRITING DESCRIPTIVE TEXT USING TEAM PAIR SOLO TECHNIQUE - Tiyas Aryani; Urai Salam; Yanti Sri Rezeki (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to develop the teaching material which can be implemented to teach descriptive text writing for the tenth-grade students of Senior High School. This study using ADDIE model to develop instructional teaching material which was adapted to meet the condition of the research. This research only implemented three phases which were analyzing, designing, and developing (ADD). The ADDIE model was selected because of its clear stages for designing a module and appropriate with educational research and development. The module was developed by observing the syllabus and textbook. The product developed combined several tasks and team pair solo as the technique. This module designed consisted of material, several tasks, and assessment that compiled with the syllabus and learning objectives stated in the 2013 curriculum. To ensure the applicability of the module, the researcher used a validation checklist from the expert to analyze. The validation checklist was used to validate the module's content. The result from experts’ validation indicated that the module was applicable as teaching material for descriptive text writing for the tenth-grade students of Senior High School due to the following features: the explanation of the text which was quite clear, the appropriate materials, and also several tasks that matched the materials.